Understanding Nicotine Dependence and Addiction Among Young Adults Who Smoke Cigarillos: A Qualitative Study. Issue 3 (10th February 2017) - Antognoli, Elizabeth; Cavallo, David; Trapl, Erika; Step, Mary; Koopman Gonzalez, Sarah; Perez, Rose; Flocke, Susan
Abstract: Introduction: Cigarillo use is increasing, particularly among young adults. Nicotine dependence (ND) is important for understanding smoking behavior and cessation, but the development of measures of ND has focused almost exclusively on cigarette smokers. We examined smoking patterns, preferences, and beliefs of cigarillo users to better understand their experience of addiction and expression of ND symptoms. Methods: Using purposive sampling, we conducted in-depth interviews between June 2015 and January 2016 with 30 young adults aged 18–28 who reported smoking ≥1 cigarillo per week. Interviews were based on a semi-structured guide designed to capture participants' smoking levels and patterns as well as their experiences of smoking and addiction. Interviews were audio-recorded and transcribed. Analysis was guided by a phenomenological approach designed to identify emergent themes. Results: Participants had a mean age of 23, with a majority being female (56%) and African American (80%). The median number of cigarillos smoked per week was 20; 70% also smoked cigarettes, and 43% also smoked marijuana blunts. Our analysis highlighted the complexity of measuring cigarillo use due to product manipulation, sharing, and multiple product use. Participants expressed a preference for smoking in a social group where cigarillos were shared, and not smoking an entire cigarillo at once when alone. Most cigarillo users did not consider themselves to be addicted. Conclusions: Cigarillo users express unique smoking practices and beliefs that signify the need for a more product-inclusive measure of ND, and can inform the development of tobacco cessation interventions tailored to cigarillo users. Implications: The increasing use of cigarillos among young adults has significant public health consequences. Addressing this issue requires accurate measurement and effective treatment of dependence on cigarillo products. The results of this study directly inform the development of a revised measure of ND, and can contribute to the efficacy of cessation interventions for cigarillo users.